2022
DOI: 10.3389/fnhum.2022.787495
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Coding Framework for Understanding Major Depression

Abstract: Predictive coding models of brain processing propose that top-down cortical signals promote efficient neural signaling by carrying predictions about incoming sensory information. These “priors” serve to constrain bottom-up signal propagation where prediction errors are carried via feedforward mechanisms. Depression, traditionally viewed as a disorder characterized by negative cognitive biases, is associated with disrupted reward prediction error encoding and signaling. Accumulating evidence also suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 128 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…This not only broadens the scope of diseases treated by coloring but also confirms the effect of coloring therapy on improving depression in patients, similar to the study by Bosman et al 29 However, the existing studies on the mechanism of action of coloring treatment to alleviate depressive symptoms in GAD patients are unclear. It has been proposed 32 that dysfunctional reinforcement learning processes and dysregulated reward circuits may partially underlie the pathology of depressive symptoms, mainly manifested by a lack of pleasure or hypersensitivity to reward, with key neural regions, including the lateral rein nucleus, ventral tegmental area, and substantia nigra, and that the severity of pleasure deficit modulates the relationship between reward expectancy and reward prediction error signals in the ventral striatum; specifically, the presence of individuals with severe pleasure deficit symptoms may have deficits in aspects related to reward learning, and patients with low reward sensitivity better understand reward prediction error signals in reward tasks; therefore, patients with depressive symptoms require more refined and targeted psychotherapeutic interventions. In our study, patients with GAD used their preferred colors and patterns for coloring creations, which not only provided a certain amount of pleasure in the short repetitive actions but also expressed stressful events related to the disease through their chosen colors, patterns, and coloring trajectories, which in turn assisted the psychotherapist in providing targeted psychotherapeutic solutions, ultimately achieving the effect of reducing depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This not only broadens the scope of diseases treated by coloring but also confirms the effect of coloring therapy on improving depression in patients, similar to the study by Bosman et al 29 However, the existing studies on the mechanism of action of coloring treatment to alleviate depressive symptoms in GAD patients are unclear. It has been proposed 32 that dysfunctional reinforcement learning processes and dysregulated reward circuits may partially underlie the pathology of depressive symptoms, mainly manifested by a lack of pleasure or hypersensitivity to reward, with key neural regions, including the lateral rein nucleus, ventral tegmental area, and substantia nigra, and that the severity of pleasure deficit modulates the relationship between reward expectancy and reward prediction error signals in the ventral striatum; specifically, the presence of individuals with severe pleasure deficit symptoms may have deficits in aspects related to reward learning, and patients with low reward sensitivity better understand reward prediction error signals in reward tasks; therefore, patients with depressive symptoms require more refined and targeted psychotherapeutic interventions. In our study, patients with GAD used their preferred colors and patterns for coloring creations, which not only provided a certain amount of pleasure in the short repetitive actions but also expressed stressful events related to the disease through their chosen colors, patterns, and coloring trajectories, which in turn assisted the psychotherapist in providing targeted psychotherapeutic solutions, ultimately achieving the effect of reducing depression.…”
Section: Discussionmentioning
confidence: 99%
“…This not only broadens the scope of diseases treated by coloring but also confirms the effect of coloring therapy on improving depression in patients, similar to the study by Bosman et al 29 However, the existing studies on the mechanism of action of coloring treatment to alleviate depressive symptoms in GAD patients are unclear. It has been proposed 32 In addition to mood disorders, depressed patients are found to have cognitive impairment, which is attributed to the abnormal reduction in the left dorsolateral prefrontal function involved in the regulation of positive emotions in depressed patients. 33 However, Silvia's 34 study found that coloring activities, in which participants integrated existing patterns and colors into new works of art, improved their creative thinking and cognitive abilities, and Daudén Roquet and Sas's 35 study also showed that coloring therapy engages patients fully in coloring activities, which can improve colorists' insight and revisit these negative emotional experiences, ultimately achieving a reduction in depressed mood.…”
Section: Coloring Therapy Can Relieve Depression Symptoms In Gad Pati...mentioning
confidence: 99%
“…Disruptions of the ANS can induce inflammation (85) and metabolic dysregulation (86). Low sensitivity to interoceptive signals may lead to disrupted predictive coding of interoceptive signals (19, 87), which is crucial to emotional processing and allostatic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Depression has been conceptualized as a disorder of inference by several researchers (reviewed recently in Gilbert et al, 2022 ). Some of these theories focused in particular on dysregulation of allostasis as the basis of depressive etiology ( Barrett et al, 2016 ; Stephan et al, 2016 ; Arnaldo et al, 2022 ).…”
Section: The Brain Integrative Generative Model Of Stress and Homeost...mentioning
confidence: 99%